2017
DOI: 10.1063/1.4975664
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dust-ion acoustic periodic travelling waves in a magnetized plasma with two temperature superthermal electrons and stationary charged dust grains

Abstract: In this research, the nonlinear propagation of dust-ion acoustic (DIA) periodic travelling waves in a dusty plasma consisting of cold ions, stationary charged dust grains, and two temperature superthermal electrons is theoretically studied. A nonlinear Zakharov-Kuznetsov equation, which describes nonlinear dust-ion acoustic waves, is derived using a reductive perturbation method. Furthermore, the bifurcation theory has been employed to study the nonlinear propagation of DIA periodic travelling wave solutions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In this sense, the bifurcation analysis of the phase portrait for the Hamiltonian of the system has been extensively employed to study the physical nature of travelling nonlinear dust acoustic waves in plasma. This analysis has significant applications in different plasma environments (Selim et al2015;Abdelwahed et al 2017;El-Shamy et al2021;Selim et al2021;Samanta et al2013;Pradhan et al 2021;Tolba 2021). For instance, Selim et al (2015) have investigated the bifurcation analysis of nonlinear ionacoustic travelling waves in a multicomponent magnetoplasma with superthermal electrons.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the bifurcation analysis of the phase portrait for the Hamiltonian of the system has been extensively employed to study the physical nature of travelling nonlinear dust acoustic waves in plasma. This analysis has significant applications in different plasma environments (Selim et al2015;Abdelwahed et al 2017;El-Shamy et al2021;Selim et al2021;Samanta et al2013;Pradhan et al 2021;Tolba 2021). For instance, Selim et al (2015) have investigated the bifurcation analysis of nonlinear ionacoustic travelling waves in a multicomponent magnetoplasma with superthermal electrons.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many investigators have applied bifurcation analysis [ 35 ] extensively to examine non‐linear waves' physical behaviour in different plasma models due to its significant applications in various plasma cases. [ 36–45 ] In particular, they discussed the probability of the existence and characteristics of periodic travelling waves. For instance, by applying the bifurcation theory, Abdelwahed et al [ 38 ] discussed the non‐linear propagation of dust‐ion acoustic periodic travelling waves in a dusty plasma consisting of cold ions, stationary charged dust grains, and two temperature superthermal electrons.…”
Section: Introductionmentioning
confidence: 99%
“…[ 36–45 ] In particular, they discussed the probability of the existence and characteristics of periodic travelling waves. For instance, by applying the bifurcation theory, Abdelwahed et al [ 38 ] discussed the non‐linear propagation of dust‐ion acoustic periodic travelling waves in a dusty plasma consisting of cold ions, stationary charged dust grains, and two temperature superthermal electrons. Abdelwahed et al found [ 38 ] that the superthermality of cold and hot electrons has a strong and weak influence, respectively, on the non‐linear dust‐ion acoustic periodic wave structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,7] Actually, particles with high-energy tails are characterized by superthermal particles. [11][12][13][14] In effect, the essential motivation for successive development in the investigation of a dusty plasma is in its wide applications in various scientific fields. Indeed, when tends to infinity, the non-Maxwellian distribution approaches the well-known Maxwellian distribution.…”
Section: Introductionmentioning
confidence: 99%